Can a symptom checklist improve the triage of patients following successful endometrial cancer treatment? - Yang Peng; Monika Janda; Andreas Obermair (Elsevier, 2020)
Endometrial cancer (EC) is the fifth most common cancer in women in developed countries. Clinical practice guidelines recommend patients should be followed-up every 3-6 months after primary treatment of EC. Evidence suggests that 40% to 80% of patients develop symptoms prior to being diagnosed with EC recurrence, however which symptoms are key remains unclear. We previously conducted a comprehensive literature review and developed a questionnaire on patient-reported symptoms associated with EC recurrence.This is a brief communication on a pilot prospective cohort study among 120 Australian patients who completed primary treatment for EC in the past three years. The study showed 47 of the 120 patients (39.2%) self-reported at least one symptom, four of whom (3.3%) were diagnosed with a recurrence. Back or lumbar pain (P = 0.012), vaginal bleeding (P < 0.001), and lethargy, fatigue, exhaustion or tiredness (P = 0.002) were significantly associated with the development of EC recurrence.The checklist will be further validated as part of a randomized controlled clinical trial to confirm the observed relationship between symptoms and the development of EC recurrence.